2020
DOI: 10.25186/.v15i.1752
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of coffee beans through computer vision and machine learning algorithms

Abstract: The increasing market interest in coffee beverage, lead coffee growers around the world to adopt more efficient methods to select the best-quality coffee beans. Currently, coffee beans selection is carried out either manually, which is a costly and unreliable process, or using electronic sorting machines, which are often inefficient because some coffee beans defects, such as sour and immature beans, have similar spectral response patterns. In this sense, the present work aimed to analyze the importance of shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
2
Order By: Relevance
“…Lima et al In layers below 25 cm, there was a reduction in SPR, a fact relating to the effect to implements applied in soil preparation; emphasis on traffic machines did not affect soil physical structure in depth, except in the no-tillage system (NT); this becomes evident when comparing Figures 2 and 3 at a 35 cm depth downwards; in this stratum the values are very similar. Lima et al [38] reported increased SPR with below-layer soil tillage. Otto et al [39] found lower SPR results than those obtained in our study, but this was demonstrated by a severely affected location, with machine traffic in the inter rows of sugarcane.…”
Section: Soil Resistance Penetration In Inter Rowsmentioning
confidence: 96%
“…Lima et al In layers below 25 cm, there was a reduction in SPR, a fact relating to the effect to implements applied in soil preparation; emphasis on traffic machines did not affect soil physical structure in depth, except in the no-tillage system (NT); this becomes evident when comparing Figures 2 and 3 at a 35 cm depth downwards; in this stratum the values are very similar. Lima et al [38] reported increased SPR with below-layer soil tillage. Otto et al [39] found lower SPR results than those obtained in our study, but this was demonstrated by a severely affected location, with machine traffic in the inter rows of sugarcane.…”
Section: Soil Resistance Penetration In Inter Rowsmentioning
confidence: 96%
“…Model HSV dimotivasi oleh sistem visual manusia. Dalam model HSV, komponen luminous (kecerahan) dipisahkan dari informasi pembawa warna (hue dan saturation) [11], [20]- [22]. Model warna HSV didefinisikan pada persamaan (11) berikut.…”
Section: Fitur Hsvunclassified
“…Pinto et al (2017) used the Convolutional Neural Network (CNN) to classify defects in raw coffee beans, achieving accuracies ranging from 72.4 to 98.7% based on the types of defects. Santos et al (2020) and García et al (2019) discussed quality control of ground coffee beans by detecting defects. Santos et al (2020) used Support Vector Machine (SVM), Random Forest (RF), and Deep Neural Network (DNN) to classify coffee beans defects according to the shape and color features, achieving high accuracy in their results.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al (2020) and García et al (2019) discussed quality control of ground coffee beans by detecting defects. Santos et al (2020) used Support Vector Machine (SVM), Random Forest (RF), and Deep Neural Network (DNN) to classify coffee beans defects according to the shape and color features, achieving high accuracy in their results.…”
Section: Introductionmentioning
confidence: 99%